Journal of Occupational Science: A Tool for Advancing International Connections for the Study of Occupation - Forwell, S; Prodinger, B; Stanley, M; Hocking, C; Rogers, S (The Society for the Study of Occupation (SSO), 2014)
Background: One indication of the growth and development of a discipline is the quality of its research publications. The Journal of Occupational Science (JOS) is the only international journal dedicated to publishing occupational science research. The journal is in its 20th year of production and holds a well-respected place in the library of occupational scientists. As the number of submissions to JOS grows each year, a rigorous review process is required to maintain the quality of the journal. Being alert to referees’ expectations will assist prospective authors to manage the review process. Intent: In this paper, members of the JOS editorial team draw on their experience of reviewing and editing manuscripts to alert prospective authors to the common issues and omissions and offer suggestions to avoid or overcome them. Examples of common problems include abstracts that lack clarity and structure, lack of attention to reporting methodological rigour, “inventing” terminology, and lack of consideration of the audience of the journal. Conference participants will learn about the JOS scope, editorial policy and publication process, including strategies for submission, writing and responding to reviews, and the resubmission process, through interaction with JOS editorial members. Information in the presentation will be particularly useful for novice authors but may also apply to those with more experience. Conclusion: There is increasing pressure from universities and employers for researchers to publish their work. However, getting published can be challenging process. Attending this presentation is an opportunity for conference participants to develop knowledge and skills that will aid in the publication process. Contribution to occupational science: Publication of occupational science studies that demonstrate conceptual clarity and methodological rigor will contribute to a strong knowledge base and growth of the discipline.